Murder at Small Koppie the real story of South Africa's Marikana massacre - Marinovich, Greg 1962- (African history and culture, 2018)
"The killing of thirty-four miners by police at Marikana in August 2012 was the largest massacre of civilians in South Africa since Sharpeville. The events have been covered in newspaper articles, on TV news and in a commission of inquiry, but there is still confusion about what happened on that fateful day. In Murder at Small Koppie, renowned photojournalist Greg Marinovich explores the truth behind the Marikana massacre. He investigates the shootings near Wonderkop hill, which happened in view of the media, as well as the killing that happened beyond the view of cameras at a nondescript collection of boulders knows as Small Koppie, some 300 metres away. Many of the men killed here were shot in cold blood at close range. Drawing on his own meticulous research, eyewitness accounts and the findings of the Marikana Commission of Inquiry, Marinovich accurately reconstructs that fateful day as well as the events leading up to the strike, and looks at the subsequent denials, obfuscation and buck-passing by Lonmin, the SAPS and the government. This is the definitive account of the Marikana massacre from the journalist whose award-winning investigation into the tragedy has been called the most important piece of South African journalism since apartheid."...Back cover